2020
DOI: 10.1101/2020.01.29.924894
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolution from adherent to suspension – systems biology of HEK293 cell line development

Abstract: 1The need for new safe and efficacious therapies has led to an increased focus on biologics 2 produced in mammalian cells. The human cell line HEK293 has bio-synthetic potential 3 for human-like production and is today used for manufacturing of several therapeutic pro-4 teins and viral vectors. Despite this increasing popularity there is still limited knowledge 5 of the detailed genetic and composition of derivatives of this strain. Here we present a 6 genomic, transcriptomic and metabolic gene analysis of six… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…The SV40 origin of replication is present on the H77 sE2 expression vector (pPPI4) we used [64]; however, it is highly improbable that an improvement in plasmid stability would affect the distal process of sE2 glycosylation. A recent omics study of the HEK 293 line and its progeny not only revealed transcriptome profile differences between adherent 293T cells and 293-F cells but also between 293H cells adapted to suspension and 293-F cells [65]. This indicates genes other than those involved in the adherent to suspension transition are also differentially expressed in 293 progeny cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The SV40 origin of replication is present on the H77 sE2 expression vector (pPPI4) we used [64]; however, it is highly improbable that an improvement in plasmid stability would affect the distal process of sE2 glycosylation. A recent omics study of the HEK 293 line and its progeny not only revealed transcriptome profile differences between adherent 293T cells and 293-F cells but also between 293H cells adapted to suspension and 293-F cells [65]. This indicates genes other than those involved in the adherent to suspension transition are also differentially expressed in 293 progeny cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The SV40 origin of replication is present on the H77 sE2 expression vector (pPPI4) we used (57); however, it is highly improbable that an improvement in plasmid stability would affect the distal process of sE2 glycosylation. A recent omics study of HEK293 and its progeny cell lines not only revealed transcriptome profile differences between adherent 293T cells and 293F cells but also between 293H cells adapted to suspension and 293F cells (58). This indicates genes other than those involved in the adherent to suspension transition are also differentially expressed 293 progeny cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…In respect to cell physiology, serum removal and anchorage-independent growth is a major change. It mimics an epithelial-to-mesenchymal transition [ 29 , 30 ] which is one of the most complex and multilayer-leveled processes that cells can undergo [ 31 ]. In fact, it is not by chance that principal component analysis identified ‘serum-containing adherent vs. serum-free suspension’ cultures as the first source of variability in the dataset, before cell bank repository origin or CAV-2 infection ( Figure 6 A).…”
Section: Discussionmentioning
confidence: 99%